Herramientas digitales y aprendizaje autónomo en estudiantes del nivel de secundaria de la Institución Educativa Primaria Secundaria N° 60053 Augusto Freyre, Iquitos 2025 - Cenepo Saquiray, Sergio Geisel (2026)
The purpose of this research was to determine the relationship between digital tools and autonomous learning in secondary school students at the secondary primary school Institución Educativa Primaria Secundaria N°60053 Augusto Freyre, Iquitos 2025. Opting for a basic study with a non-experimental, correlational and cross sectional design, the sample consisted of 70 secondary school students for the survey conducted with two questionnaires for data collection. The findings show that, in the variable Digital tools, 42.8% are at a high level; on the variable Autonomous learning, 38.6% are at a high level. Therefore, it is determined that there is a moderate positive correlation between the variables by a coefficient of rho=0.698 and a significance p=0.006 ( <0.05). Likewise, the technological dimension shows a moderate positive correlation (rho=0.676) and significant (p=0.001); similarly, the informational dimension shows a moderate positive correlation (rho=0.682) and significant (p=0.000); finally, the communicative dimension shows a moderate positive correlation (rho=0.543) and significant (p=0.002), these dimensions are significantly related to the Autonomous Learning variable.